Authentic leadership rediscovering the secrets to creating lasting value - George, Bill. (San Francisco Jossey-Bass, 2003)
In the wake of continuing corporate scandals there have been few, if any, CEOs that have stepped forward as models of "doing things right"?except the former chairman and CEO of Medtronic, Bill George. George has become the unofficial spokesperson for responsible leadership?in business, the media, and academia.
Includes index
Keywords: Leadership